Perencanaan dan Perancangan Pusat Pemerintahan Baru di Kabupaten Garut Bagian Selatan Dengan Konsep Pendekatan Arsitektur Neo Vernakular - Ahmad Aguswin; Hasanudin Hasanudin (DPPM Universitas Pelita Bangsa, 2022)
West Java is a province whose territory is divided into regency and city areas. Each regency and city area has a regional government which is regulated by law. Garut Regency is one of the regencies in West Java province which in its development process has progressed and developed quite significantly, both from the economic, socio-cultural, and political sectors. Regional expansion can be regarded as a strategic government step to improve the implementation of government tasks both in the context of service, empowerment and development towards the realization of an advanced, independent and prosperous society. to accelerate the surrounding community to make government administration so that people who are located far from the city center are easier to manage. The theme that will be used in the Planning and Design of the new Government Center in the Southern Garut Regency with the concept of the Neo-Vernacular Architecture approach itself is a blend of architectural styles. modern with traditional architectural style. Because for a modern era like today, many traditional values are gradually fading away. Keywords: Garut Regency, Regional Expansion, Neo-Vernacular Architecture